A journey through digital storytelling during COVID-19 Students preparedness to use technology for learning in the language classroom - Elma Marais (Research in Social Sciences and Technology, 2021)
The COVID-19 pandemic has forced lecturers at South African universities to reconceptualise their teaching and learning activities. Universities had to embark on remote teaching to salvage the 2020 academic year. This created the opportunity to draw on students’ creative and digital skills to promote digital storytelling as a way of enhancing their learning experience. This article describes the journey of a teacher educator and a group of students registered for a language didactics module in an initial teacher education programme. Film study was traditionally presented through lively conversations in a contact session where students could exchange their perceptions and opinions regarding various aspects of film. Because of the COVID-19 lockdown this approach had to be reviewed. The lecturer in question employed digital learning competencies to transform learning through the innovative use of digital tools and resources to rethink student engagement with film. Students were invited to create digital stories. The outcome of the process not only improved their understanding of teaching film but also promoted their digital competencies and empowered them to create resources they could use in their careers.